Antihero configuration and time - Cappello, Giancarlo (2008)
If the hero figure has been traditionally associated with better times, a time that won’t come back; if he’s the pragmatic ideal that inspires the future, he must be imitated, he must be reached; if the hero belongs to the victors stance; if men and arts sublime and put him in comfortable glory; if his image goes around as a figure of joy that we build and internalize through a variety of stories in which we devote ourselves to his virtues: ¿What have happened with this modernity hero? This text attempts to investigate the time and characteristics of these characters of modernity that are classified as nonheroic, but nevertheless have won our regard and today wear the same golden band of the famous.